(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
The SLC1 family of sodium dependent transporters includes the plasma membrane located glutamate transporters and the neutral amino acid transporters ASCT1 and ASCT2 [1, 49, 36, 37, 7].